2020
DOI: 10.3390/math8030348
|View full text |Cite
|
Sign up to set email alerts
|

Some Notes on the Formation of a Pair in Pairs Trading

Abstract: The main goal of the paper is to introduce different models to calculate the amount of money that must be allocated to each stock in a statistical arbitrage technique known as pairs trading. The traditional allocation strategy is based on an equal weight methodology. However, we will show how, with an optimal allocation, the performance of pairs trading increases significantly. Four methodologies are proposed to set up the optimal allocation. These methodologies are based on distance, correlation, cointegratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…To calculate the value of b, we will use the method described by Ramos-Requena et al [55], called minimizing distance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the value of b, we will use the method described by Ramos-Requena et al [55], called minimizing distance.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, all of these contributions are focused on the methodology for pairs selection. In a different line, Ramos-Requena et al [55] introduced different models to calculate the amount of money that must be allocated to each stock. The authors showed these new alternatives perform better than the usual Equal Weight method.…”
Section: Fundamentals Of Pairs Tradingmentioning
confidence: 99%
“…Once the 50 stocks with the lowest volatility have been selected, we select the pairs from that 50-stock universe. In order to do that, we follow the method defined by Ramos-Requena et al [31] (see also [45]). Given a pair candidate of stocks A and B, we define the pair series as s(b)(t) � p A (t) −bp B (t), where p A (t) is the logarithm of the price of stock A at time t, p B (t) is the logarithm of the price of stock B at time t and b is the quantity invested in stock B for each dollar invested in stock A.…”
Section: Pairs Trading Strategymentioning
confidence: 99%
“…To calculate the value of b, we will use a method introduced in [56,68] that is based on the volatility of stock returns. This factor is calculated as:…”
Section: Pairs Trading Strategymentioning
confidence: 99%